Cause of kidney disease and cardiovascular events in a national cohort of US patients with end-stage renal disease on dialysis: a retrospective analysis. (2nd August 2018) - O'Shaughnessy, Michelle M; Liu, Sai; Montez-Rath, Maria E; Lafayette, Richard A; Winkelmayer, Wolfgang C
Abstract: Aims: End-stage renal disease (ESRD) is a strong cardiovascular risk factor. We aimed to determine the extent to which cause of kidney disease independently contributes to this risk. Methods and results: Using a national US ESRD registry, we selected patients with eight different causes of ESRD who initiated dialysis 1997–2014. We used proportional sub-distribution hazard models, with non-cardiovascular death or kidney transplantation as competing risks, to estimate hazard ratios (HRs) for a first composite cardiovascular event (myocardial infarction, ischaemic stroke, or cardiovascular or cerebrovascular death), by cause of ESRD. The population was restricted to those using Medicare insurance at Day 91 after dialysis initiation (when most patients become Medicare eligible). Outcomes were ascertained from Medicare claims or Death Notifications. Among the 658 168 patients identified, composite event rates ranged from 3.5/100 person-years in IgA nephropathy to 14.6/100 person-years in diabetic nephropathy (DN). After adjusting for demographics, socioeconomic factors, comorbidities, dialysis modality, and laboratory values, cardiovascular event HRs differed significantly by cause of ESRD. Comparing to IgA nephropathy, the adjusted HR was highest for DN [aHR = 2.97, 95% confidence interval (CI) 2.77–3.20], next highest for lupus nephritis (aHR = 1.86, 95% CI 1.71–2.03), and thereafter ranged from 1.29 (95% CI 1.19–1.39) in autosomal dominant polycystic kidney disease to 1.67 (95% CI 1.52–1.83) in membranous nephropathy. Conclusion: High cardiovascular event rates in dialysis patients vary considerably by cause of ESRD. Determining underlying reasons for these differences might provide new insights in to cardiovascular disease mechanisms as well as inform future drug development and clinical trial design.